2011
DOI: 10.1007/s00234-011-0892-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse vascular injury: convergent-type hemorrhage in the supratentorial white matter on susceptibility-weighted image in cases of severe traumatic brain damage

Abstract: Supratentorial massive hemorrhages and supratentorial convergent-type multiple hemorrhages were associated with poor prognosis after traumatic brain injury. The increased diffusivity in lobes with convergent-type hemorrhages may indicate that congestion of the proximal medullary vein may play some role for these hemorrhages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 14 publications
(18 reference statements)
0
26
0
Order By: Relevance
“…Notably, a prior study by Iwamura et al characterized supratentorial deep white matter hemorrhages and proposed a four-grade classification system based on their degree and distribution: 1) small hemorrhage, 2) single bead-like hemorrhage, 3) convergent-type hemorrhage, 4) and “massive hemorrhage” [29]. A limitation of this approach, however, is that the radiologic classification of brainstem lesions is based on the histopathological model proposed by JH Adams, in which all brainstem lesions are classified as “grade 3.” Moreover, brainstem microbleeds were not specifically analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, a prior study by Iwamura et al characterized supratentorial deep white matter hemorrhages and proposed a four-grade classification system based on their degree and distribution: 1) small hemorrhage, 2) single bead-like hemorrhage, 3) convergent-type hemorrhage, 4) and “massive hemorrhage” [29]. A limitation of this approach, however, is that the radiologic classification of brainstem lesions is based on the histopathological model proposed by JH Adams, in which all brainstem lesions are classified as “grade 3.” Moreover, brainstem microbleeds were not specifically analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The corpus callosum, deep grey nuclei, brain stem and cerebellum are often involved. 85 The major differential diagnosis is DAI. The number and anatomic distribution of the haemorrhages allow differentiation from DAI ( Figure 10).…”
Section: Diffuse Vascular Injurymentioning
confidence: 99%
“…In the last few years, several articles have been published on the application of SWI in patients with TBI. 5,9,10,15,17,18,33,45,46,51,58,82,94,95,[99][100][101] …”
Section: Swi In Neurotraumatologymentioning
confidence: 99%
“…Various studies have demonstrated the effectiveness of SWI in outcome prediction using SWI for hemorrhage grading, 51 the dichotomization of patients with and those without CMBs, 29,33 or the detection of a greater number and volume of lesions. 5,9,94,95,99 Despite having various SWI methods for outcome prediction, the current state of research has yet to reveal which method would exhibit the highest accuracy and specificity in predicting outcome and recovery.…”
Section: 82 Outcome Predictionmentioning
confidence: 99%
See 1 more Smart Citation